2000
DOI: 10.1103/physreve.62.7861
|View full text |Cite
|
Sign up to set email alerts
|

Chaos and coherence in the conservative three-mode decay interaction

Abstract: In this work we analyze the influence of chaos on the coherence of the mismatched three-wave interaction. Chaos starts to play a decisive role in the problem when adiabatic approximations leading to an integrable model for the system cease to be valid. In regular regimes where the field levels are sufficiently small, there is a characteristic value for the frequency mismatch of the triplet below which coherence and phase locking are dominant. In chaotic regimes, on the other hand, there is no such value and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…We considered a simplified three dimensional model with inhomogeneous electromagnetic fields. Using a Hamiltonian formalism and the concept of limiting curves, 19,20 we were able to determine conditions that guarantee the confinement of the electron in the acceleration channel. It was also shown that as a given parameter of the electromagnetic field is changed, the particle trajectory could transit from regular to chaotic without affecting the confinement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We considered a simplified three dimensional model with inhomogeneous electromagnetic fields. Using a Hamiltonian formalism and the concept of limiting curves, 19,20 we were able to determine conditions that guarantee the confinement of the electron in the acceleration channel. It was also shown that as a given parameter of the electromagnetic field is changed, the particle trajectory could transit from regular to chaotic without affecting the confinement.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, we take advantage of the concept of limiting curves. 19,20 The procedure to obtain these curves is as follows. Isolating z in the Hamiltonian (8) we can write z ¼ z(r, P r , P z ; H, P h ).…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact is that although the high-frequency tends to be a fixed parameter for each of the interacting modes, the low-frequency associated to the modulational process grows with the amplitudes or the coupling strength of the involved waves. If at large enough amplitudes or coupling strengths the modulational frequency becomes comparable to the frequency of the carriers, the modulational approximation fails [6,7].…”
Section: Introductionmentioning
confidence: 96%
“…3(c) is really bounded; a limiting curve [27] at I ≈ 0.1 acts as a barrier that completely limits the particle energy gain. On the other hand, the full system (2) is higher-dimensional and Arnold diffusion could play a role [13,22].…”
Section: Reduced Hamiltonianmentioning
confidence: 99%